Katarina Elizabeta baronica Raumschüssl, rojena Sauer, in njena loretska kapela pri celjskih minoritih - Bence, Gorazd (Studia Historica Slovenica, 2021)
On 30 June 1692, the widowed Baroness Katharina Elisabeth Raumschüssl from the family of Counts Sauer of Borl established the sung Litany of the Blessed Virgin Mary in the Celje Minorite monastery. This previously overlooked deed of gift is important not only as a testimony to the Baroness’s pious intentions and the connections between the Sauers and the Celje Minorites but also because of its reference to the Loreto chapel in the monastery church, whose extension and furnishing the Baroness financed as well, according to the deed. The chapel is another in a series of copies of the Holy House of Loreto, Mary’s house from Nazareth, many of which were also constructed in Styria by the end of the 17th century, especially by noble patrons. The article presents the Baroness’s family background, related to the veneration of Our Lady of Loreto, and discusses the most probable location and reconstruction of the chapel. Based on the interpretation of Ignacij Orožen’s record and the 1813 plan of the monastery, the present article presents a well-argued thesis that the Loreto chapel was once located on the site nowadays occupied by the chapel of Our Lady of Lourdes in the succursal (formerly Minorite) Church of the Assumption of Mary in Celje.
Keywords: Celje (Slovenia); Celje Minorite monastery; Cerkvena arhitektura; church architecture; church art; Kapele; Krščanska likovna umetnost; Krščanski samostani; Loreto chapel; Mecenstvo; Raumschüssl, Katarina Elizabeta; Santa Casa; Sauer, Jurij Friderik; umetnostna zgodovina